Beauty and women in the works by Yasunari Kawabata and Rabindranath Tagore - Do, Thu Ha (Vietnam National University, Hanoi, 2020)
Great thoughts often meet. The paper considers the similarities in the way Yasunari Kawabata (Japan) and Rabindranath Tagore (India) talked about beauty and women in their master pieces